Asset Price, the Exchange Rate, and Trade Balances in China: A Sign Restriction VAR Approach - Wongi Wongi (East Asian Economic Review (EAER), 2018)
Although asset price is an important factor in determining changes in external balances, no studies have investigated it from the Chinese perspective. In this study, I empirically examine the underlying driving forces of China's trade balances, particularly the role of asset price and the real exchange rate. To this end, I estimate a sign-restricted structural vector autoregressive model with quarterly time series data for China, using the Bayesian method. The results show that changes in asset price affect China's trade balances through private consumption and investment. Also, an appreciation of the real exchange rate tends to deteriorate trade balances in China. Furthermore, forecast error variance decomposition results indicate that changes in asset price (stock price and housing price) explain about 20% variability of trade balances, while changes in the real exchange rate can explain about 10%.
Keywords: C32; F14; F41; 330; Stock Price; Housing Price; Real Effective Exchange Rate; China Trade Balance; Sign Restriction VAR